The daughter of Rome - Hunt, Angela Elwell, 1957- (Hunt, Angela Elwell, 1957- Emissaries, 2025)
"In Nero's Rome, a catastrophic fire leaves Calandra reliant on a group of Christians. She grapples with her mistrust but finds herself indebted to those who helped rebuild her shattered world. When Nero blames the tragedy on the Jewish Messiah's followers, Calandra is forced to choose between right and wrong, friends and family, love and death"--